(untitled) (Research, Society and Development, 2024)
This research aims to quantify the greenhouse gas emissions from vehicles and discuss the impacts of replacing fossil fuels with natural gas in Mozambique. Using the COPERT 5.7 (EMISIA) methodology and also the EMEP/EEA Guidebook proposed by the European Environment Agency (EEA), the study provides detailed data on the vehicle fleet from 2013 to 2020, including fuel consumption and emissions of various gases. The findings highlight the need for maintenance and adherence to emission standards to reduce pollution. The use of vehicular gas requires careful handling techniques to prevent methane leakage. The implementation of global air quality guidelines is a national emergency. The research suggests the electrification of transport and the production of "green hydrogen" as strategies to reduce emissions. However, the energy transition is a complex challenge that requires a multifaceted approach and future studies in this area are essential.